Pengaruh Kecerdasan Intrapersonal Terhadap Penyesuaian Diri Siswa Di Sma Negeri 9 Manado - Paul M. Heydemans; Rinna Y. Kasenda; Ariantje J. A. Sundah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of intrapersonal intelligence on student self-adjustment at SMA Negeri 9 Manado. The population in this study was regular 10th-grade students with a total of 501, with 84 students as subjects. The data collection technique is a questionnaire and documentation with validity and reliability test instruments. The data analysis technique is simple linear regression analysis. Before analyzing the data to test the hypothesis, the Inferential analysis requirements test was first carried out, namely the Normality test and Linearity test with the help of the SPSS (Statistical Package for service solution) 22 for Windows computer program. Based on the results of a simple regression test, the regression equation Y = 35.054 + 0.456 X. And this result means that if there is an increase in the Intrapersonal Intelligence variable, the student's Adjustment variable will increase, and from these results, it is evident that there is a significant influence between Intrapersonal Intelligence on Self-Adjustment student.